Latest Triassic and Early Jurassic Spiriferinida (Brachiopoda) of Zealandia(New Zealand and New Caledonia) - Macfarlan, Donald Alexander Bankier (Zootaxa, 2023)
The Late Triassic spiriferinides of Zealandia include the endemic or Austral genera Rastelligera, Psioidea and Psioidiella, and the cosmopolitan Zugmayerella. Mentzelia kawhiana is revised and placed in Callospiriferina. It appears in the late Rhaetian and is found in the Téremba Terrane in New Caledonia and throughout the Murihiku Terrane in New Zealand. The spiriferinides were severely affected at the Triassic–Jurassic boundary in Zealandia as elsewhere, but a moderately diverse fauna developed in the Early Jurassic. This has strong links to South America, and affinities with southern Europe and North Africa. In this study, a total of six species of Jurassic spiriferinides are recognised. Callospiriferina ongley is present in middle and late Hettangian and Sinemurian faunas. It is succeeded in the Pliensbachian and early Toarcian by Callospiriferina radiata. Two species of Spiriferina are recognised. S. sophiaealbae n. sp. first appears in the Middle Hettangian and is present in the Southland and Kawhia Synclines until the early Toarcian. S. arakiwa n. sp. is found mainly on the southwest limb of the Southland Syncline in the Pliensbachian and early Toarcian. The non-costate European genus Cisnerospira is represented in Zealandia by the small C. antipoda n. sp. This species ranges from Hettangian to early Toarcian. Two specimens of a spiriferinide with a costate sulcus are tentatively identified as Dispiriferina sp. cf. D. chilensis. The highest stratigraphic level at which Zealandian spiriferinides have been found is that of the Dactylioceras band at Kawhia, which is correlated with the Crassum Subzone of the Bifrons Zone (highest Early Toarcian) and includes three species of spiriferinide. This suggests that the Zealandian spiriferinides survived the Toarcian Event, only to meet their demise slightly later.